1972
DOI: 10.1017/s0079497x00012056
|View full text |Cite
|
Sign up to set email alerts
|

The Excavation of a Neolithic Settlement on Broome Heath, Ditchingham, Norfolk, England

Abstract: The excavation of the earthwork and part of the interior of a C-shaped enclosure in south Norfolk produced evidence of a Neolithic occupation from the mid fourth to the late third millennium B.C. The earthwork was constructed at the end of the third millennium B.C. and palaeobotanical analyses of the fossil soil beneath it produced information concerning the environment of the time. Quantities of pot-sherds and stone tools were recorded from the earthwork and from clusters of pits, and a study of grain impress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…Parallels for the incomplete enclosure, or angled ditch at Etton Woodgate I, are few, but there is a superficial resemblance to Broome Heath (Wainwright 1972). A closer parallel is, however, provided by recent excavations at Court Hill, Singleton, West Sussex, where an earthwork enclosure (very approximately 200 m. by 200 m.) is accompanied by an open C-shaped ditch/enclosure slightly further down the hill.…”
Section: The Archaeological Backgroundmentioning
confidence: 99%
“…Parallels for the incomplete enclosure, or angled ditch at Etton Woodgate I, are few, but there is a superficial resemblance to Broome Heath (Wainwright 1972). A closer parallel is, however, provided by recent excavations at Court Hill, Singleton, West Sussex, where an earthwork enclosure (very approximately 200 m. by 200 m.) is accompanied by an open C-shaped ditch/enclosure slightly further down the hill.…”
Section: The Archaeological Backgroundmentioning
confidence: 99%
“…This site has been interpreted as a settlement on the basis of a large number of pits and a considerable amount of domestic debris (Wainwright 1972). In East Anglia, there is Broome Heath, an unusual C-shaped earthwork substantial enough to be considered defensive.…”
Section: Neolithic Non-causewayed Enclosures In Southern Englandmentioning
confidence: 99%
“…Typological phasing would largely depend on the derivation of shouldered vessels from pre-existing east coast traditions related to the northern Grimston variant. It has, however, been recently demonstrated that this plain ware tradition continues in a relatively intact state through the third millennium at Broome Heath (Wainwright 1972), pre-supposing its coexistence but not co-ordination with the regional Mildenhall style. Separation of the Orsett material by levels has not been successful in relating stratigraphic succession to stylistic changes.…”
Section: {B) the Potterymentioning
confidence: 99%
“…Frequently the site topography (and in the past, perhaps vegetation) will have strongly influenced the siting and layout of the enclosure, but this is more clearly demonstrated on continental sites than those in England. One Middle Neolithic site in East Anglia which has been proven by area excavation to be C-shaped is that at Broome Heath, where the enclosure is dated to 2217 ±78 be (BM-755) (Wainwright 1972). It is significant that the Broome Heath interior produced no definite evidence of settlement contemporary with the earthwork.…”
mentioning
confidence: 99%